Connection Domain Mutations N348I and A360V in HIV-1 Reverse Transcriptase Enhance Resistance to 3′-Azido-3′-deoxythymidine through Both RNase H-dependent and -independent Mechanisms - Ehteshami, Maryam (American Society for Biochemistry and Molecular Biology, 2008)
Thymidine analogue-associated mutations (TAMs) in reverse transcriptase (RT) of the human immunodeficiency virus type 1 (HIV-1) cause resistance to 3′-azido-3′-deoxythymidine (AZT) through excision of the incorporated monophosphate. Mutations in the connection domain of HIV-1 RT can augment AZT resistance. It has been suggested that these mutations compromise RNase H cleavage, providing more time for AZT excision to occur. However, the underlying mechanism remains elusive. Here, we focused on connection mutations N348I and A360V that are frequently observed in clinical samples of treatment-experienced patients. We show that both N348I and A360V, in combination with TAMs, decrease the efficiency of RNase H cleavage and increase excision of AZT in the presence of the pyrophosphate donor ATP. The TAMs/N348I/A360V mutant accumulates transiently formed, shorter hybrids that can rebind to RT before the template is irreversibly degraded. These hybrids dissociate selectively from the RNase H-competent complex, whereas binding in the polymerase-competent mode is either not affected with N348I or modestly improved with A360V. Both connection domain mutations can compensate for TAM-mediated deficits in processive DNA synthesis, and experiments with RNase H negative mutant enzymes confirm an RNase H-independent contribution to increased levels of resistance to AZT. Moreover, the combination of diminished RNase H cleavage and increased processivity renders the use of both PP(i) and ATP advantageous, whereas classic TAMs solely enhance the ATP-dependent reaction. Taken together, our findings demonstrate that distinct, complementary mechanisms can contribute to higher levels of excision of AZT, which in turn can amplify resistance to this drug.